PENGARUH LITERASI KEUANGAN KECERDASAN SPIRITUAL DAN PENDIDIKAN KEUANGAN DI KELUARGA TERHADAP PENGELOLAAN KEUANGAN MAHASISWA - Madelberta Resma Nugraheni Sigo; Lilik Sri Hariani; Walipah Walipah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
This study aims to analyze the effect of financial literacy, spiritual intelligence, and financial education in families on the financial management of students of Economic Education in Kanjuruhan University Malang. This type of research uses quantitative research, using multiple linear regression. The population in this study were all students of Economic Education at Kanjuruhan University Malang, totaling 198 students with a research sample of 65 students. The sampling technique in this study used quota sampling. The data obtained were analyzed using the SPSS application version 16.00 for windows. Based on the results of the analysis it is known that there is a significant simultaneous and partial effect between financial literacy, spiritual intelligence, and financial education in families on the financial management of students of Economic Education at Universitas Kanjuruhan Malang.